Assessment of genetic diversity and mating system of Acacia cyclops restoration and remnant populations. Issue 6 (5th August 2019) - Millar, Melissa A.; Coates, David J.; Byrne, Margaret; Krauss, Siegfried L.; Jonson, Justin; Hopper, Stephen D.
Abstract : Acacia cyclops, or Ngaamarur, is a common coastal shrub or small tree of the southwest of Western Australia and South Australia used for restoration in these landscapes and elsewhere. Knowledge of genetic diversity and mating systems of restoration populations is often lacking but can help inform likely restoration success. We compared genetic diversity and mating system parameters at three restoration populations of A. cyclops to nearby remnant reference populations. Mean levels of genetic diversity in restoration populations ( Na = 1.806, Ne = 1.560, He = 0.270, Ho = 0.359) were not significantly different from those in the reference populations ( Na = 1.833, Ne = 1.574, He = 0.269, Ho = 0.352) suggesting diverse seed collections were made for restoration. Allelic genetic divergence among restoration and reference populations was low ( D ST ≤ 0.04) suggesting that seeds were of local provenance. Mating system parameters were similar among restoration (tm = 0.989, tm –ts = 0.010, rpm = 0.392) and reference populations (tm = 0.868, tm –ts = 0.039, rpm = 0.410), suggesting functionality of the mating system and restitution of generalist insect pollinator services in restored populations at 7, 10, and 12 years after planting. Lower levels of heterozygosity in progeny compared to adults suggest post‐germination or late‐acting selection against inbred seedlings. Evidence for selection and seedling attrition further emphasizes the benefits of collections from many individuals in well‐connected outcrossed source populations. Overall, results suggest available local genetic diversity was captured and restoration populations have mating systems equivalent to those of reference populations.